Determinants of related and unrelated export diversification - Muhammad Ali (Economies, 2017)
This paper contributes to the literature on determinants of the export diversification by introducing related variety (RV) and unrelated variety (UV) in the analysis in addition to the traditional entropy based measure at three-digit Standard International Trade Classification (SITC) level, overall variety (OV). RV measures variety in cognitively related industries, while UV measures variety in industries that are unrelated to each other. Studies on RV and UV have shown that the dynamics of their relationship with economic growth and innovation may differ and one would expect that the determinants of RV and UV may also be different. Therefore, using data on manufacturing sector exports for 130 countries from 1996 to 2011, this paper identifies the determinants of export diversification with primary focus on foreign direct investment as an external source of knowledge and a stimulus to entrepreneurship and human capital as a measure of productive capabilities. Considering the concern of endogeneity bias, estimations of the econometric models were performed using generalized method of moments. Findings show that some of the determinants of diversification affect RV, UV and OV differently. For instance, foreign direct investment (FDI) negatively affects RV while it has no significant relationship with OV and UV. Moreover, interaction of human capital with FDI appears to be positive and significant for UV and RV while interaction of human capital with trade openness is significant and positive for RV only, showing the importance of knowledge through external sources in the process of related diversification.
Keywords: F14; F21; O33; 330; export diversification; related variety; unrelated variety; human capital; foreign direct investment; Generalized Method of Moments